Cross-National Perspectives on Aging and Place: Implications for Age-Friendly Cities and Communities. (15th November 2021) - Woolrych, Ryan; Sixsmith, Judith; Duvvuru, Jamuna; Portella, Adriana; Fang, Mei Lan; Menezes, Deborah; Henderson, James; Fisher, Jenny; Lawthom, Rebecca
Abstract: Background and Objectives: The age-friendly cities and communities (AFCC) agenda has led to a range of policy initiatives aimed at supporting aging in place for older people. While there is case study evidence of how people age across urban contexts, there has been little research exploring cross-national understandings of age-friendly places among older people. The objective of this article is to identify the place experiences of older people living across cities and communities in India, Brazil, and the United Kingdom and to discuss implications for the AFCC agenda. Research Design and Methods: A total of 300 semistructured interviews were undertaken with older people across 9 cities and 27 communities in India, Brazil, and the United Kingdom. The data were analyzed using thematic analysis undertaken by each national team and then discussed and revised at collaborative workshops with researchers from each of the 3 country teams. Results: The data capture the ways in which place is constructed from the perspective of older people drawing upon social, community, and cultural dimensions of aging across diverse urban environments. We explore how older people negotiate place in the context of their everyday life and identify the relational and interconnected ways in which place attachment, belonging, and identity are constructed. Discussion and Implications: Age-friendly interventions need to attend to the changing physical, social and cultural dimensions of aging and place. Integrated place-making practices are required to support older people to age in the right place across rapidly transforming urban contexts globally.